Hubungan Antara Pengetahuan Kesehatan Reproduksi Dengan Perilaku Seks Pranikah - Nurron, Badariyah; , Dra. Zahrotul Uyun, M. Si, Psi (2016)
For teenagers who are already sexually mature not only want to learn about sexuality issues but also desire to interact and attract the opposite sex. It encourages teenagers to have a relationship with the opposite sex without thinking whether it is healthy or not for their reproductive health. The purpose of this research is to understand The Relations between Reproductive Health Knowledge and Premarital Sexual Behavior; to examine reproductive health knowledge of teenagers; to understand premarital sexual behavior rate of teenagers. The hypothesis of this research is: there is a negative relationship between reproductive sexual knowledge and premarital sexual behavior. This research is quantitative research. The subject of this research is 105 High School Students which are on grade IX. This research uses questioners about reproductive health knowledge and premarital sexual behavior. This research applies random sampling technique as method. Based on the calculation using product moment, the correlation coefficient value (r xy) is -0,078 (p > 0,05) which means that there is no relations between reproductive health knowledge and premarital sexual behavior. The result of the research also shows that reproductive health knowledge and premarital sexual behavior rate is considered low.